Intracellular localization of sphingosine kinase 1 alters access to substrate pools but does not affect the degradative fate of sphingosine-1-phosphate[S] - Deanna L. Siow (Journal of Lipid Research, 2010)
Sphingosine kinase 1 (SK1) produces sphingosine-1-phosphate (S1P), a potent signaling lipid. The subcellular localization of SK1 can dictate its signaling function. Here, we use artificial targeting of SK1 to either the plasma membrane (PM) or the endoplasmic reticulum (ER) to test the effects of compartmentalization of SK1 on substrate utilization and downstream metabolism of S1P. Expression of untargeted or ER-targeted SK1, but surprisingly not PM-targeted SK1, results in a dramatic increase in the phosphorylation of dihydrosphingosine, a metabolic precursor in de novo ceramide synthesis. Conversely, knockdown of endogenous SK1 diminishes both dihydrosphingosine-1-phosphate and S1P levels. We tested the effects of SK1 localization on degradation of S1P by depletion of the ER-localized S1P phosphatases and lyase. Remarkably, S1P produced at the PM was degraded to the same extent as that produced in the ER. This indicates that there is an efficient mechanism for the transport of S1P from the PM to the ER. In acute labeling experiments, we find that S1P degradation is primarily driven by lyase cleavage of S1P. Counterintuitively, when S1P-specific phosphatases are depleted, acute labeling of S1P is significantly reduced, indicative of a phosphatase-dependent recycling process. We conclude that the localization of SK1 influences the substrate pools that it has access to and that S1P can rapidly translocate from the site where it is synthesized to other intracellular sites.51: 2546–2559.